CO2 hydrogenation to methanol over Rh/In2O3–ZrO2 catalyst with improved activity - Zhe Lu; Jing Wang; Kaihang Sun; Shilong Xiong; Zhitao Zhang; Chang-jun Liu (Green Chemical Engineering, 2022)
The In2O3 supported rhodium catalyst has been previously confirmed to be active for CO2 hydrogenation to methanol. In this work, the In2O3–ZrO2 solid solution was prepared and employed to support the rhodium catalyst. The deposition-precipitation method was applied to make the Rh catalyst highly dispersed. The catalyst characterization confirms that the use of ZrO2 optimizes and stabilizes the oxygen vacancies of In2O3, which causes the enhanced adsorption and activation of CO2. The highly dispersed Rh catalyst remarkably improves the hydrogenation ability of the In2O3–ZrO2 support. Compared to Rh/In2O3, the In2O3–ZrO2 supported Rh catalyst shows significantly higher activity with high methanol selectivity. For instance, at 300 °C and 5 MPa, the methanol selectivity over Rh/In2O3–ZrO2 reaches 66.5% with a space-time yield (STY) of methanol of 0.684 gMeOH h-1 gcat-1 and a CO2 conversion of 18.1%. The methanol selectivity and methanol STY at 300 °C is 19% and 26% higher than that of the Rh/In2O3 catalyst.